BIOCHEMICAL CONTENTS OF BRAIN IN THE FRESHWATER FISH, NOTOPTERUS NOTOPTERUS NOTOPTERUS NOTOPTERUS (PALLAS) IN RELATION TO SEX - SHAHANA BANU; R. S. KULKARNI; KHAJA PASHA (The Bioscan, 2009)
The concentration of some biomolecules of the brain in the freshwater fish, Notopterus notopterus has been studied to understand the biochemical differentiation of the brain in relation to sex. The biomolecules such as protein, glycogen, lipids and cholesterol were estimated in the brain of freshwater fish, Notopterus notopterus of both the sex for comparative assessment. The results indicate that the amount of biomolecules of brain of male fish were higher in comparison to the amount of biomolecules of brain of female fish. The result suggests that the concentration of protein found to be higher in male brain as compared to the female brain. Protein acts both as nutrient and as an energy source. The study of brain glycogen in both female and male reveals that male brain has more glycogen content than the female brain. The variation in the glycogen content in female brain and male brain are due to differences in sex. The comparison of lipid content in brain in both sexes show that male brain has more lipids than female. The data shows that only female brain has more cholesterol than the male brain. The above results indicate that the brain of male and female is biochemically different probably based on their metabolic activity.